The Effect of Training Based on the SCORPIO Model on the Knowledge and Skills of Airway Management Peri-Anesthesia Induction in Undergraduate of Nursing Anesthesiology Students - Masoumeh Albooghobeish; Zinat Mohammadi; Ali Khalafi; Morteza Habibi moghadam (Archives of Anesthesia and Critical Care)
Background: Using novel educational methods in teaching medical sciences is very important. The SCORPIO model is one such method that can be used as an interactive educational station and a combination of other educational methods. The purpose of this study was to determine the effectiveness of the SCORPIO model in the acquisition of knowledge and skills of airway management during peri-anesthesia induction among undergraduate nursing anesthesia students. Methods: The present study was a randomized controlled study with a pre-test-post-test design including an intervention and a control group. The participants were undergraduate nursing anesthesia students studying in the 3rd and 5th semesters. Sixty students were selected using convenience method and were randomly assigned to intervention and control groups. In order to collect data, a researcher-made questionnaire was used to assess the students’ knowledge and an OSCE test to assess their skills. The intervention group attended three 2-hour training sessions where the knowledge and skills of airway management during peri-anesthesia induction was taught using the SCORPIO model. The control group, on the other hand, received the same content through conventional teaching methods including lectures and the use of manikins in three 2-hour sessions. Results: There was no statistically significant difference between the two groups in terms of demographic characteristics (p<0.05). The mean score of students' knowledge of airway management during peri-anesthesia induction before the intervention was (1.83) 12.47 in the intervention group and (1.71) 12.63 in the control group. Also, the mean score of students' skill of airway management during peri-anesthesia induction before the intervention was (1.44) 12.07 in the intervention group and (1.43) 12.43 in the control group, which indicated no statistically significant difference according to independent t-test (p=0.71 and p=0.32, respectively). After the intervention, however, the results of the paired t-test showed a statistically significant difference between the two groups in terms of the knowledge and skill scores, with the students in the intervention group obtaining higher scores of knowledge and skills (p<0.001), while this was not the case in the control group (p=0.26 and p=0.64, respectively). Conclusion: The SCORPIO model improves the knowledge and skills of airway management peri-anesthesia induction in undergraduate nursing anesthesia students